A bioflocculant from Corynebacterium glutamicum and its application in acid mine wastewater treatment - Liu, Yinlu; Zeng, Yan; Yang, Jiangang; Chen, Peng; Sun, Yuanxia; Wang, Min; Ma, Yanhe (Frontiers in Bioengineering and Biotechnology, 2023)
Although many microorganisms have been found to produce bioflocculants, and bioflocculants have been considered as attractive alternatives to chemical flocculants in wastewater treatment, there are few reports on bioflocculants from the safe strain Corynebacterium glutamicum, and the application of bioflocculants in acid wastewater treatment is also rare attributed to the high content of metal ions and high acidity of the water. In this study, a novel bioflocculant produced by C. glutamicum Cg1-P30 was investigated. An optimal production of this bioflocculant with a yield of 0.52 g/L was achieved by Box–Behnken design, using 12.20 g/L glucose, 4.00 g/L corn steep liquor and 3.60 g/L urea as carbon and nitrogen source. The structural characterization revealed that the bioflocculant was mainly composed of 37.50% neutral sugar, 10.03% uronic acid, 6.32% aminosugar and 16.51% protein. Carboxyl, amine and hydroxyl groups were the functional groups in flocculation. The biofocculant was thermally stable and dependent on metal ions and acidic pH, showing a good flocculating activity of 91.92% at the dosage of 25 mg/L by aid of 1.0 mM Fe3+ at pH 2.0. Due to these unique properties, the bioflocculant could efficiently remove metal ions such as Fe, Al, Zn, and Pb from the real acid mine wastewater sample without pH adjustment, and meanwhile made the acid mine wastewater solution become clear with an increased neutral pH. These findings suggested the great potential application of the non-toxic bioflocculant from C. glutamicum Cg1-P30 in acid mine wastewater treatment.